1999
DOI: 10.1038/sj.bjc.6690392
|View full text |Cite
|
Sign up to set email alerts
|

An audit of breast cancer pathology reporting in Australia in 1995

Abstract: The pathologist's role in breast cancer management is to make a diagnosis and report key items of information essential to treatment planning. To increase national uniformity in procedures and reporting, the Australian Cancer Network's (ACN) Pathology Working Party released specific recommendations about pathology reporting of breast cancer specimens in 1997 (ACN Pathology Working Party, 1997). These recommendations were that all microscopic reports of invasive breast cancer should contain information on tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
1
10
1
Order By: Relevance
“…Prior to the release of the recommendations tumour type and size were found to be given in reports of invasive breast cancer for 93% of women, 70% had, in addition, grade and clearance of the margins while only 28% had all recommended information. 16 In comparison our reports documented tumour type in 92% of cases but only documented tumour size in 50% of cases. The presence or absence of tumour cells in the resection margin, which determines the completeness or otherwise of surgical procedure, was documented in only 64% of our cases.…”
Section: Discussionmentioning
confidence: 58%
“…Prior to the release of the recommendations tumour type and size were found to be given in reports of invasive breast cancer for 93% of women, 70% had, in addition, grade and clearance of the margins while only 28% had all recommended information. 16 In comparison our reports documented tumour type in 92% of cases but only documented tumour size in 50% of cases. The presence or absence of tumour cells in the resection margin, which determines the completeness or otherwise of surgical procedure, was documented in only 64% of our cases.…”
Section: Discussionmentioning
confidence: 58%
“…Variation in growth rate might also underlie the significant, independent association of architecture with tumour size. The pathology reports from 1998 to 2000 reported DCIS substantially more completely than did earlier Australian reports (Kricker et al, 1999;Giles et al, 2001;Shugg et al, 2002). The Australian Cancer Network addressed pathology reporting of DCIS with extensive consultation among pathologists in the mid-1990s and published recommendations in 1997 (Australian Cancer Network Working Party, 1997(Australian Cancer Network Working Party, 2001.…”
Section: Discussionmentioning
confidence: 93%
“…Two experienced Cancer Registry personnel extracted information on the type of specimen, size, grade, architecture, presence or absence of necrosis and multifocality of DCIS, and clearance and width of the margins from pathology reports (Kricker et al, 1999).…”
Section: Datamentioning
confidence: 99%
“… 23 , 24 Compared with first audits in HICs, only 64.7% had complete reports according to the College of American Pathologists guidelines in an audit from 2010, 25 and only 28% fulfilled all recommendations in an audit from Australia in 1995. 26 Report completeness improves over time, and with ongoing audits, more recent European studies have shown > 94% complete reports according to EUSOMA standards. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%